PENGETAHUAN DAN ASUPAN ZAT GIZI IBU HAMIL (ENERGI, PROTEIN DAN ZAT BESI) - Santi Aprilian Lestaluhu (Jurnal Kebidanan, 2021)
A mother’s level of knowledge about adequate nutrition dramatically influences the behavior of good food choices so that mothers can choose nutritious foods and arrange a balanced menu according to their body’s needs during pregnancy. It will have significant effect on their baby’s birth weight. This study aims to describe the mothers’ knowledge about nutrients and their nutritional intake level during pregnancy. The descriptive study was conducted on 34 respondents who had their pregnancy checked at Passo Public Health Center. The result showed that mostly the knowledge of pregnant women about nutrients was in moderate category (41,17%). Meanwhile their nutritional intake level was mostly in less category (energy 52,94%, protein 55,88% and iron 44,12%). It can be concluded that the knowledge about nutrients and the nutritional intake of pregnant women in Passo Public Health Center need to be improved to ensure mother and child health in the fututre.